NUMERICAL COMPUTATION OF DIFFERENT ASPECTS OF 26 DECEMBER 2004 TSUNAMI ALONG THE PENANG ISLAND USING A CYLINDRICAL POLAR MODEL - Md. Fazlul. Karim (Proceedings of ICMSA, 2006)
The tsunami of December 26, 2004 was devastating in its effect on the island of Penang. A numerical model based on the linear shallow-water equations in cylindrical polar coordinate system was discussed and the results presented in a previous study ( Roy and Izani, 2005). In this study we investigate the effects of using a more refined grid on the wave height distribution along the coastline of Penang. We also study the effect of changing the orientation of the source. Our studies show that the more refined grid is capable of generating wave heights in good agreement with observed data without excessively increasing the computation time. It is also found that orientation of the source have a significant effect on the wave heights.